Developmental reading 2 - Marquez, Servillano T.; Casela, Neliza C. ; Sadorra, Bryan Eli (Quezon City, 2009)
Emergent literacy is viewed in this book as the natural and active process of constructing meaning of young learners which is facilitated by interactive and child-centered classrooms for reading instruction. Further, this book significantly recognizes children as emergent readers and emergent writers as they take literacy information from their home and as they naturally develop their learning prior to any kind of formal instruction
Keywords: Reading Comprehension